The relationship between causal beliefs and desire for social distance towards people with schizophrenia and depression: Results from a survey of young Ghanaian adults. (January 2019) - Franke, Miriam Leona; Lersner, Ulrike von; Essel, Osuanyi Quaicoo; Adorjan, Kristina; Schomerus, Georg; Gómez-Carrillo, Ana; Tam Ta, Thi Minh; Böge, Kerem; Mobashery, Mahan; Dettling, Michael; Diefenbacher, Albert; Angermeyer, Matthias C.; et al.
Highlights: This study gives first insights about causal beliefs and desire for social distance in young Ghanaian population. There is stigma attached to people with depression and schizophrenia. Childhood adversities is significantly associated with more social distance. Respondants from the northern part of Ghana show significantly less desire for social distance. Female respondents exhibited higher desire for social distance towards depression. Abstract: This study examines attitudes of the young Ghanaian population regarding the relationship between causal beliefs and desire for social distance from people with symptoms of schizophrenia and depression. Respondents ( n  = 507) were presented with depression and schizophrenia symptoms using unlabeled case vignettes. A factor analysis examined three factors for causal beliefs, and multiple linear regression analysis on the desire for social distance was conducted. The desire for social distance was higher when symptoms in both case-vignettes were attributed to childhood adversities and overall lower when respondents lived in northern regions of Ghana. Only, for vignettes depicting schizophrenia, mental illness attribution was associated with more desire for social distance. Significant gender effects were found for depression vignettes only: female respondents reported significantly more desire for social distance, whereas female gendered vignettes were associated with less desire for social distance by respondents of both genders.